Implementing White Box Testing for Evaluating the Inner Logic Code of the Research, Staffs, and Library Information System of Institute of Informatics and Business Darmajaya - Anggi Andriyadi; Dona Yuliawati; Sushanty Saleh; Bobby Bachry (Proceeding International Conference on Information Technology and Business, 2020)
Evaluating system was the common steps needed to be done before the system was run online. One of the familiar system that was usually used was Blackbox Testing or White box Testing. Blackbox testing was used to test the user interface system and Whitebox testing was used to test the inner logic of system. This study used the Whitebox testing to test the inner code of the Research, Staffs, and Library Information System of Institute of Informatics and Business Darmajaya. The test covered 3 steps e.g., creating the flowgraph notation, 2) finding the cyclomatic complexity, and 3) conducting the test case. The result of this study was that the algorithm had 22 nodes and 25 edges. Cyclomatic Complexity formula was created to find 5 cases maximally. These cases were tested so that the system was passed. Therefore, it proved that the system was run and the Whitebox testing was good options for evaluating inner system